2021
DOI: 10.1093/plphys/kiaa120
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy is required for lipid homeostasis during dark-induced senescence

Abstract: Autophagy is an evolutionarily conserved mechanism that mediates the degradation of cytoplasmic components in eukaryotic cells. In plants, autophagy has been extensively associated with the recycling of proteins during carbon-starvation conditions. Even though lipids constitute a significant energy reserve, our understanding of the function of autophagy in the management of cell lipid reserves and components remains fragmented. To further investigate the significance of autophagy in lipid metabolism, we perfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 79 publications
3
31
0
Order By: Relevance
“…TEM analyses revealed that both the outer and inner envelopes of chloroplast and thylakoid membranes of the fhy3 far1 plants lost their plasticity and flexibility during the extended darkness treatment, and thus failed to rapidly respond to the dark-light transition (Figure 2a). A recent study revealed that lipid remodelling is critical in plant rapid responses to extended darkness condition (Barros et al, 2021). Under extended darkness conditions, chloroplast membrane lipids are degraded and release fatty acids and stored triacylglycerols (TAGs) in lipid droplets in the cytosol, which can donate substrates for beta-oxidation (Barros et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TEM analyses revealed that both the outer and inner envelopes of chloroplast and thylakoid membranes of the fhy3 far1 plants lost their plasticity and flexibility during the extended darkness treatment, and thus failed to rapidly respond to the dark-light transition (Figure 2a). A recent study revealed that lipid remodelling is critical in plant rapid responses to extended darkness condition (Barros et al, 2021). Under extended darkness conditions, chloroplast membrane lipids are degraded and release fatty acids and stored triacylglycerols (TAGs) in lipid droplets in the cytosol, which can donate substrates for beta-oxidation (Barros et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that lipid remodelling is critical in plant rapid responses to extended darkness condition (Barros et al, 2021). Under extended darkness conditions, chloroplast membrane lipids are degraded and release fatty acids and stored triacylglycerols (TAGs) in lipid droplets in the cytosol, which can donate substrates for beta-oxidation (Barros et al, 2021). The high expression of multiple autophagy response genes (ATG7, ATG8a, 8h and 8i) and altered ultrastructure of chloroplast membranes in the fhy3 far1 plants (Figures 2 and 3) indicated that FHY3 and FAR1 might also regulate lipid homeostasis of chloroplast membranes under extended darkness conditions by an unknown mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Once again, the degradation of chloroplast lipids was observed in the atg mutants, like in the aforementioned studies. However, unlike in the experiments performed under N or S limitations [ 191 ], Barros and colleagues observed an accumulation of plastid-derived TAG and of plastoglobuli in atg mutants [ 202 ]. However, despite TAG accumulation under dark stress, autophagy mutants contained surprisingly less LDs.…”
Section: Autophagy Rewires Cellular Activities To Mediate Plant Adaptation To Stress: the Complex Relationship Between Autophagy And Lipimentioning
confidence: 99%
“…Given that this lipophagy phenotype resembled a micro-autophagy process and could be blocked by the atg2-1 mutation, the authors assumed that LD micro-autophagy requires the macro-autophagy core machinery. More recently, lipidomic analyses on the Arabidopsis atg5 , atg7, and atg9 autophagy mutants grown under dark conditions confirmed that autophagy affects the homeostasis of multiple lipid families [ 202 ]. Once again, the degradation of chloroplast lipids was observed in the atg mutants, like in the aforementioned studies.…”
Section: Autophagy Rewires Cellular Activities To Mediate Plant Adaptation To Stress: the Complex Relationship Between Autophagy And Lipimentioning
confidence: 99%
“…Similarly, under combined dark and salinity stress, the marine microalgae Dunaliella tertiolecta was found to increase lipid content from 28% to 39% during 36 hours of dark [29]. Dark-induced senescence of the vascular plant Arabidopsis thaliana demonstrated an accumulation of triacylglycerides (TAGs) and lipoproteins via autophagy [30]. The process of autophagy (a mechanism induced by stress) in eukaryotic microalgae has been linked to increases in TAGs [31] and the degradation of ribosomal proteins [32] through nutrient starvation, but has yet to be linked to dark-induced stress.…”
Section: Introductionmentioning
confidence: 99%